Wage System Analysis in CV. Jemn’d in The City of Ambon - Lesnussa, Johny Urbanus (Pinisi Business Administration Review, 2023)
The problem in this research is how the wage system on CV. JeMn'D Ambon. The purpose of doing this research is to find out how the wage system on CV. JeMn'D. The data used in this study is a qualitative descriptive data analysis technique. To achieve the objectives of this study, data collection was carried out with the help of interviews and giving questionnaires to obtain data.Based on the results of data analysis, it can be concluded that the wages/salaries received by employees of CV. JeMn'D in the shop section is Rp. 1,300,000/month and the supermarket section gets a wage of Rp.1,500,000/month. The salary/wages received by employees are not in accordance with the Maluku Provincial Minimum Wage (UMP), which is Rp. 2,604,960. In accordance with the Government Regulation on Proper Living Needs, the wages received by JeMn'D employees cannot meet their daily needs. Working time on CV. JeMn'D before the Ambon Mayor Regulation regarding PPKM was 19 working hours/day, while after PPKM it was 9 working hours/day. There is a government rule that if the length of time worked exceeds the limit, the employee is entitled to receive overtime wages/salary. But this did not happen to CV. JeMn'D, the employee's working time has exceeded the limit of government regulations regarding the length of working hours, but the employee does not receive overtime wages/salary. On CV. JeMn'D also provides a Holiday Allowance (THR) to its employees, namely on major religious holidays in accordance with the religion of each employee, namely THR in the amount of salary per month plus holiday gifts in the form of food and drinks. On CV. JeMn'D also has a regulation in place, namely if an employee is intentionally absent from work without notification and a permit or sick note, a fine of Rp. 10,000/day. JeMn'D also provides a Holiday Allowance (THR) to its employees, namely on major religious holidays in accordance with the religion of each employee, namely THR in the amount of salary per month plus holiday gifts in the form of food and drinks. On CV. JeMn'D also has a regulation in place, namely if an employee is intentionally absent from work without notification and a permit or sick note, a fine of Rp. 10,000/day. JeMn'D also provides a Holiday Allowance (THR) to its employees, namely on major religious holidays in accordance with the religion of each employee, namely THR in the amount of salary per month plus holiday gifts in the form of food and drinks. On CV. JeMn'D also has a regulation in place, namely if an employee is intentionally absent from work without notification and a permit or sick note, a fine of Rp. 10,000/day.